ORGANIZATION AND STAGES OF EXPERIMENTAL WORK ON DEVELOPING HISTORICAL THINKING OF PRE-SERVICE HISTORY TEACHERS THROUGH MUSEUM PEDAGOGY - Niyozov Javlonbek Jakhongir ugli (Web of Journals Publishing, 2026)
This article explores the organization and staged implementation of experimental work aimed at developing historical thinking among pre-service history teachers through museum pedagogy. The study reconceptualizes the museum environment not as a supplementary excursion space but as an educational laboratory in which historical knowledge is constructed through systematic engagement with material evidence, primary sources, and cultural heritage. Employing a quasi-experimental research design, the study is organized as a continuous classroom–museum–classroom didactic cycle comprising diagnostic, formative, and control stages. The article details participant selection criteria, procedures for ensuring comparability between experimental and control groups, assessment instruments, evaluation criteria, and ethical considerations. Special emphasis is placed on aligning instructional and assessment practices with core operations of historical thinking, including source-based reasoning, contextualization, causal explanation, interpretation, and reflective analysis. The study demonstrates that museum pedagogy, when methodologically structured, constitutes an effective resource for strengthening procedural dimensions of historical thinking in history teacher education.
Keywords: Museum pedagogy; historical thinking; pre-service history teachers; quasi-experimental design; reflection.